Development of clinical models for predicting erectile function after localized prostate cancer treatment. (23rd July 2014) - Haskins, Amy E; Han, Paul KJ; Lucas, Frances L; Bristol, Ian; Hansen, Moritz
<x xml:space="preserve">Abstract</x> Objectives To develop clinical prediction models estimating the probability of maintaining erections adequate for intercourse 2 years after prostate cancer treatment, based on pretreatment characteristics. Methods Study participants consisted of prostate cancer patients with localized disease and functional erections before undergoing surgery (n = 536) or radiation therapy (n = 240) at a single USA institution. Baseline patient‐ and treatment‐related data were collected from a clinical database and through chart review. Erectile function at 2 years post‐treatment was prospectively assessed through a self‐administered single‐item measure. Multivariate logistic regression using backward selection was used to derive clinical prediction models to predict erectile function at 2 years for surgery and radiation therapy patients; the models were internally validated using bootstrapping methods. Results The final prediction model for surgery patients included the predictor variables of age, body mass index, smoking, diabetes, hypertension and nerve‐sparing procedures, whereas the model for radiation therapy patients included hypertension, risk category and radiation technique. The new models showed acceptable calibration and discrimination: c‐statistic = 0.71 (95% confidence interval 0.68–0.76) for surgery and 0.66 (95% confidence interval 0.61–0.74) for radiation therapy models. Conclusions New clinical prediction models based on patient and treatment characteristics show promising accuracy in predicting erectile function at 2 years in patients treated with surgery and radiation for localized prostate cancer. More work is required to confirm and validate these models in different patient populations.